Diplomasi Pertahanan Indonesia dengan Negara-Negara Di Asia Tenggara Untuk Meningkatkan Kapabilitas Militer (Indonesian Defense Diplomacy with Countries in Southeast Asia To Improve Military Capabilities) - Yusro, Muhammad Rizki; Sinaga, Obsatar; Darmawan, Wawan Budi (Jurnal Inspirasi, 2020)
The dynamics in the Southeast Asian region has fluctuated, from traditional threats to non-traditional threats. In responding to these changes, ASEAN and member countries formulated policies in the form of defense diplomacy to create security and maintain regional stability for the creation of a harmonious climate. This research purposes to explain and justify that one of the factors for increasing military capacity and capability is defense diplomacy conducted by countries in the Southeast Asian region, especially Indonesia. This research used a qualitative method with data collection using primary data in the form of interviews with informants and using secondary data, namely documentation studies. Based on the results of this study, defense diplomacy conducted by Indonesia and member countries within ASEAN is one of the factors in increasing military capacity and capability in creating a stable, harmonious and equal region.